2007
DOI: 10.1523/jneurosci.4302-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Ankyrin-Dependent and -Independent Mechanisms Orchestrate Axonal Compartmentalization of L1 Family Members Neurofascin and L1/Neuron–Glia Cell Adhesion Molecule

Abstract: Axonal initial segments (IS) and nodes of Ranvier are functionally important membrane subdomains in which the clustering of electrogenic channels enables action potential initiation and propagation. In addition, the initial segment contributes to neuronal polarity by serving as a diffusion barrier. To study the mechanisms of axonal compartmentalization, we focused on two L1 family of cell adhesion molecules (L1-CAMs) [L1/neuron-glia cell adhesion molecule (L1/NgCAM) and neurofascin (NF)] and two neuronal ankyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 79 publications
8
115
0
Order By: Relevance
“…Released Kv3.1b channel proteins may cross the AIS barrier through intracellular transport mediated by motor proteins and/or passive diffusion. Finally, it is important to note that our studies do not exclude the involvement of other proteins in the targeting process, because precise targeting of neuronal membrane proteins likely requires multiple steps (Boiko et al, 2007). Our results suggest that ankyrin G plays a key role in controlling axon-dendrite targeting of Kv3.1 channels, and lay the foundation for additional studies aimed at a complete understanding of Kv3 channel targeting and function in neurons.…”
Section: Direct Interaction Between the T1 Domain And The Atm Regionmentioning
confidence: 88%
“…Released Kv3.1b channel proteins may cross the AIS barrier through intracellular transport mediated by motor proteins and/or passive diffusion. Finally, it is important to note that our studies do not exclude the involvement of other proteins in the targeting process, because precise targeting of neuronal membrane proteins likely requires multiple steps (Boiko et al, 2007). Our results suggest that ankyrin G plays a key role in controlling axon-dendrite targeting of Kv3.1 channels, and lay the foundation for additional studies aimed at a complete understanding of Kv3 channel targeting and function in neurons.…”
Section: Direct Interaction Between the T1 Domain And The Atm Regionmentioning
confidence: 88%
“…It has been previously shown that L1 mainly interacts with ankyrinB (Boiko et al, 2007), which in turns stabilizes L1 within the axon. Moreover, other members of the L1CAM family of cell adhesion molecules, such as neurofascin and NrCAM, interact with ankyrinG (Bennett and Chen, 2001), which mediates clustering of Na + channels at the AIS Barry et al, 2014).…”
Section: Deletion Of L1 Reduces Neuronal Intrinsic Excitability Of Exmentioning
confidence: 99%
“…3A and Fig. S4) (19). We next used surface plasmon resonance (SPR) experiments to assess the direct interaction between EB3 and ankG.…”
Section: Eb3mentioning
confidence: 99%